How To Quantify the Efficiency Potential of Neat Perovskite Films: Perovskite Semiconductors with an Implied Efficiency Exceeding 28%. Issue 17 (12th March 2020) - Stolterfoht, Martin; Grischek, Max; Caprioglio, Pietro; Wolff, Christian M.; Gutierrez‐Partida, Emilio; Peña‐Camargo, Francisco; Rothhardt, Daniel; Zhang, Shanshan; Raoufi, Meysam; Wolansky, Jakob; Abdi‐Jalebi, Mojtaba; Stranks, Samuel D.; et al.
Abstract: Perovskite photovoltaic (PV) cells have demonstrated power conversion efficiencies (PCE) that are close to those of monocrystalline silicon cells; however, in contrast to silicon PV, perovskites are not limited by Auger recombination under 1‐sun illumination. Nevertheless, compared to GaAs and monocrystalline silicon PV, perovskite cells have significantly lower fill factors due to a combination of resistive and non‐radiative recombination losses. This necessitates a deeper understanding of the underlying loss mechanisms and in particular the ideality factor of the cell. By measuring the intensity dependence of the external open‐circuit voltage and the internal quasi‐Fermi level splitting (QFLS), the transport resistance‐free efficiency of the complete cell as well as the efficiency potential of any neat perovskite film with or without attached transport layers are quantified. Moreover, intensity‐dependent QFLS measurements on different perovskite compositions allows for disentangling of the impact of the interfaces and the perovskite surface on the non‐radiative fill factor and open‐circuit voltage loss. It is found that potassium‐passivated triple cation perovskite films stand out by their exceptionally high implied PCEs > 28%, which could be achieved with ideal transport layers. Finally, strategies are presented to reduce both the ideality factor and transport losses to push the efficiency to the thermodynamic limit. Abstract : A method is introduced to experimentally measure the efficiency potential of any neat perovskite film on glass with/without attached transport layers using intensity‐dependent photoluminescence measurements. This approach allows decoupling efficiency losses due to insufficient charge transport, bulk, interface, and surface recombination. These findings also shine light on the ideality factor in perovskite solar cells and thereby fill factor limitations.